2004
DOI: 10.1007/s00347-004-0990-8
|View full text |Cite
|
Sign up to set email alerts
|

Phake Intraokularlinsen

Abstract: Phakic intraocular lenses (PIOLs), which are located closer to the eye's nodal points than the anterior corneal surface, can provide superior optical quality for higher corrections because of retention of normal prolate corneal asphericity and larger effective optical zones. Improvements in the material and design of phakic intraocular lenses and their insertion devices combined with advances in the understanding of the anatomical and physiological interactions of the PIOLs with intraocular structures, have in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…Iris-fixated pIOLs have been associated with several surgical complications such as elevation of IOP, cataracts, pigment deposits, pupil ovalization and chronic anterior segment inflammation. [20] In this study, elevation of IOP was observed in three eyes, all of which have responded well to topical antiglaucoma drops. Glaucoma may be related to the design of pIOL or elevation of IOP may be associated with chronic anterior segment inflammation caused by iris-fixated pIOLs.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Iris-fixated pIOLs have been associated with several surgical complications such as elevation of IOP, cataracts, pigment deposits, pupil ovalization and chronic anterior segment inflammation. [20] In this study, elevation of IOP was observed in three eyes, all of which have responded well to topical antiglaucoma drops. Glaucoma may be related to the design of pIOL or elevation of IOP may be associated with chronic anterior segment inflammation caused by iris-fixated pIOLs.…”
Section: Discussionmentioning
confidence: 67%
“…Additionally, a shallow anterior chamber, extensive eye rubbing, or IOL dislocation resulting from inadequate iris enclavation are among several factors that may cause significant endothelial cell loss in eyes with iris-fixated pIOL. [20] Progressive endothelial damage may be associated with potential mechanical contacts between the pIOL and corneal endothelium. Several studies have reported short- and long-term complications related to these lenses.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies showing the usage of UBM in cornea, lens surgery, and pathophysiology of glaucoma (6–7–8–9101112). Based on these studies, it is possible to get important information on dynamic functions of iris, accommodation, presbyopia, glaucoma, and other aspects of anterior segment physiology.…”
Section: Introductionmentioning
confidence: 99%
“…The foldable model (Artiflex/Veriflex), which can be implanted through a self-sealing 3.2 to 3.5 mm clear corneal incision, is available in Europe. 1,2 Ensuring safe intraocular distances between the pIOL and crucial intraocular tissues (eg, corneal endothelium and crystalline lens) postoperatively is mandatory for the long-term safety of this type of refractive correction. To exclude poor candidates for pIOL implantation (ie, those with a protruding iris or a poor peripheral anterior chamber depth [ACD]), careful preoperative selection is required.…”
mentioning
confidence: 99%